Movement Disorders: A Video Atlas - Bhidayasiri, Roongroj; Tarsy, Daniel (Current Clinical Neurology, 2012)
Movement Disorders: A Video Atlas is a practical and concise title offering an introduction to the field of movement disorders, which is expanding rapidly with the involvement of various disciplines and specialties. The unique feature of the book is the accompanying video content, comprising common cases in each category of movement disorders.  The video clips come from Dr. Tarsy's personal video collection at Beth Israel Deaconess Medical Center and Dr. Bhidayasiri's personal collection at Chulalongkorn University and UCLA.  The video is on an accompanying DVD and can also be found at www.springerimages.com/Tarsy.  Each case includes expert narration from Dr. Tarsy. Rather than focusing on rare cases, the authors emphasize typical cases, with good history and physical signs.  Unique, easy to read, with highly instructive supporting video content,  Movement Disorders: A Video Atlas is an indispensable reference for all clinicians interested in the fascinating field of movement disorders